Sarcoidosis presenting as non‐scarring non‐scalp alopecia. (30th March 2015) - Dan, Luke; Relic, John
Abstract: In this article we describe a 39‐year‐old man who presented with non‐scarring non‐scalp alopecia of his limbs as the initial presentation of sarcoidosis. Alopecia is a rare cutaneous manifestation of sarcoidosis. A literature review has found only one other example of sarcoidosis presenting as non‐scarring non‐scalp alopecia in an area other than the scalp in a patient who was otherwise asymptomatic. Several reported cases have described scarring alopecia of the scalp, which is the area of skin most commonly affected by sarcoidosis. There has been one documented case of sarcoidosis manifesting as total body non‐scarring alopecia in a patient who had systemic symptoms of sarcoidosis. Other cases have presented rare cutaneous manifestations of sarcoidosis but in all these cases several other organ systems have been involved, and the patient has had systemic symptoms on presentation or the cutaneous presentation did not include non‐scalp non‐scarring alopecia.